Translation of oncolytic viruses in sarcoma - Steven I. Robinson; Roya E. Rochell; Velia Penza; Shruthi Naik (Molecular Therapy: Oncology)
Sarcomas are a rare and highly diverse group of malignancies of mesenchymal origin. While sarcomas are generally considered resistant to immunotherapy, recent studies indicate subtype-specific differences in clinical response to checkpoint inhibitors (CPIs) that are associated with distinct immune phenotypes present in sarcoma subtypes. Oncolytic viruses (OVs) are designed to selectively infect and kill tumor cells and induce intratumoral immune infiltration, enhancing immunogenicity and thereby sensitizing tumors to immunotherapy. Herein we review the accumulated clinical data evaluating OVs in sarcoma. Small numbers of patients with sarcoma were enrolled in early-stage OV trials as part of larger solid tumor cohorts demonstrating safety but providing limited insight into the biological effects due to the low patient numbers and lack of histologic grouping. Several recent studies have investigated talimogene laherparepvec (T-VEC), an approved oncolytic herpes simplex virus (HSV-1), in combination therapy regimens in sarcoma patient cohorts. These studies have shown promising responses in heavily pre-treated and immunotherapy-resistant patients associated with increased intratumoral immune infiltration. As new and more potent OVs enter the clinical arena, prospective evaluation in subtype-specific cohorts with correlative studies to define biomarkers of response will be critical to advancing this promising approach for sarcoma therapy.